Aligning early childhood science teaching beliefs, practices, and children’s learning outcomes: the impact of a professional development program - Chen, Shiyi; Sermeno, Rebecca; Hodge, Kathryn Nikki; Geesa, Rachel Louise; Song, Hyuksoon S.; Izci, Burcu; Froh, Zoe; Murphy, Sydney (Frontiers in Psychology, 2025)
IntroductionScience teaching belief-practice alignment is critical for ensuring high-quality, effective instruction that supports young children’s learning and engagement in science. The goal of this study is to examine the alignment between preschool and kindergarten teachers’ self-reported science teaching beliefs and observed practices before and after a science teaching professional development (PD) program and to explore whether the alignment is associated with children’s science learning outcomes. The research questions are: (1) Whether and to what extent do science teaching beliefs and practices align before and after the PD program? (2) Whether and to what extent are science teaching beliefs associated with children’s inquiry skills before and after the PD program?MethodsA total of 22 preschool and kindergarten teachers and 159 children (Mage = 47.78 months) from a Northwest state in the U.S. participated in a science teaching PD program. Teachers’ self-reported science teaching efficacy and observed teaching practices and children’s directly assessed science inquiry skills were measured before and after a one-year science PD program.ResultsMultilevel regression results revealed that science teaching beliefs were not correlated with practice before the PD but were significantly aligned following its completion. Further, while teachers’ science teaching beliefs were not associated with children’s inquiry skills before the PD, a positive correlation emerged after the PD.DiscussionOur findings suggest the potential of targeted PD programs in fostering early childhood teachers’ science teaching belief-practice alignment. The results also indicate that teachers’ science teaching beliefs may not be a robust predictor of children’s science learning outcomes unless they are aligned with teaching practices.